2000
DOI: 10.1063/1.1288145
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum ultraviolet photochemistry of CH4 and isotopomers. II. Product channel fields and absorption spectra

Abstract: In part I of this work the relative velocities and anisotropies of the atomic H and D fragments from methane photolysis at 10.2 eV were measured. In this paper the relative abundance of the methyl and methylene fragments are reported. A complete set of quantum yields for the different photodissociation channels of each isotopomer is obtained by combining the two sets of data. Previously it was found that H atoms are almost four times more likely than D atoms to be ejected; now it is found that hydrogen molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 17 publications
5
68
0
Order By: Relevance
“…Information on the chemical dynamics was gained by fitting these TOF spectra and the angular distribution in the laboratory frame (LABORATORY) using a forward-convolution routine. [24][25][26] This approach initially assumed an angular distribution T(θ) and a translational energy distribution P(E T ) in the center-of-mass reference frame (CM). TOF spectra and the laboratory angular distribution were then calculated from these center-of-mass functions.…”
Section: Methodsmentioning
confidence: 99%
“…Information on the chemical dynamics was gained by fitting these TOF spectra and the angular distribution in the laboratory frame (LABORATORY) using a forward-convolution routine. [24][25][26] This approach initially assumed an angular distribution T(θ) and a translational energy distribution P(E T ) in the center-of-mass reference frame (CM). TOF spectra and the laboratory angular distribution were then calculated from these center-of-mass functions.…”
Section: Methodsmentioning
confidence: 99%
“…Some time ago, somewhat coarse-grained spectra of CH 4 and CD 4 were reported which showed that at 10.2 eV CD 4 absorbed about 20% more strongly than CH 4 . 12 Wang et al 9 have measured the spectra of CH 3 D and found that the spectrum is almost identical in shape and strength to that of CH 4 . When we used the same absorption cross section for CH 4 and CD 4 as 485 atm…”
Section: Resultsmentioning
confidence: 99%
“…Using the Lyα photolysis of H 2 O as a reference, Brownsword et al 7 were able to establish the absolute quantum yield for the H atom formation for CH 4 at Lyα, Φ H = 0.47 ± 0.11. More recently, Wang et al 9 reported a complete set of quantum yields for the different photodissociation channels of methane and its isotopomers. Comparing quantum yields from several research groups, the values were a little different.…”
Section: Introductionmentioning
confidence: 99%
“…The excited-state orbital is essentially a 3s Rydberg-type orbital. Excitation to the excited states leads to dissociation of methane to CH 2 þ H 2 and CH 3 þ H, which has been studied experimentally 18,[36][37][38][39] and theoretically. [40][41][42] Recent ab initio calculations 42 and experiments 38,39 suggest that photodissociation of gaseous methane occurs after intersystem crossing to the T 1 state or internal conversion to the S 0 ground state.…”
Section: Photochemistry Of Saturated Hydrocarbonsmentioning
confidence: 99%